ARTIFICIAL INTELLIGENCE AND BIG DATA IN ENHANCING DECISION-MAKING EFFECTIVENESS: A SYSTEMATIC LITERATURE REVIEW - Dara Anindya Putri Umagapi; Nuril Huda; Sopiah (RADJA PUBLIKA, 2025)
Advances in digital technology have transformed the way organizations make decisions. Artificial Intelligence (AI) and Big Data Analytics (BDA) are now key foundations for improving the effectiveness of strategic and operational decisions. This study examines the contribution of AI and BDA to the effectiveness of organizational decision-making through a Systematic Literature Review approach with the PRISM protocol. A total of 20 articles from Scopus published in 2020–2025 were analyzed descriptively, thematically, and through content analysis. The results show that AI accelerates, directs, and improves decision fairness, while BDA strengthens data-driven accuracy and prediction. The integration of the two forms an adaptive and intelligent decision-making system. These findings emphasize the relevance of dynamic capability and absorptive capacity theories, as well as the importance of infrastructure readiness, analytical competency, and technology governance within organizations. This study contributes theoretically and provides strategic direction for organizations in the digital transformation process of their decision-making.